A Stepwise Approach To A National Hepatitis C Screening Strategy In Malaysia To Meet The Who 2030 Targets: Proposed Strategy, Coverage, And Costs - Lindsey Hiebert; Robert Hecht; Shan Soe-Lin; Rosmawati Mohamed; Fatiha H Shabaruddin; Syed Mukhtar Syed Mansor; Maznah Dahlui; Amirah Azzeri; Scott A McDonald (Elsevier, 2024)
Value in Health Regional Issues Volume 18, May 2019, Pages 112-120